2007
DOI: 10.1292/jvms.69.339
|View full text |Cite
|
Sign up to set email alerts
|

Persorption Mechanisms of Luminal Antigenic Particulates via Apoptotic Epithelial Cells of Intestinal Villi into Systemic Blood Circulation in Orally Immunized Rats

Abstract: ABSTRACT. The possibility of persorption of prefixed bovine serum albumin-coated sheep erythrocytes (BSA-SEs) from mucous epithelial cells and its mechanisms were investigated in rats orally immunized by BSA for 14 consecutive days. On the day after the final oral immunization, the rats were duodenally perfused by BSA-SEs or non-coated SEs. BSA-SEs were also duodenally perfused in nonimmunized rats. Thirty min after perfusion, BSA-SEs were significantly more engulfed by late-apoptotic-stage villous columnar ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…Antigenic macromolecules and particulates and their specific antibodies are also absorbed by epithelial cells at the late stage of apoptosis in orally pre-immunized rats [28,29]. In the present study, the absorption of Fc-SEs was exclusively found in epithelial cells with morphological signs of apoptosis.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Antigenic macromolecules and particulates and their specific antibodies are also absorbed by epithelial cells at the late stage of apoptosis in orally pre-immunized rats [28,29]. In the present study, the absorption of Fc-SEs was exclusively found in epithelial cells with morphological signs of apoptosis.…”
Section: Discussionsupporting
confidence: 55%
“…On the other hand, duodenally administered BSA-SEs are histologically found in the blood vessels of the liver, but not in lymph vessels or mesenteric lymph nodes in orally pre-BSA-immunized rats. Therefore, the SEs taken up by epithelial cells are considered to be directly transported to the portal blood and finally reach the systemic blood circulation [28]. In the present findings, Fc-SEs passed through the endothelium of the subepithelial blood capillaries and were present in the capillary lumen, but not in the lymph vessels.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…These portions are also epithelial cell-shedding sites and accumulation sites of epithelial cells in the late-apoptotic stage in rats [30,33,34]. These accumulation sites of epithelial cells in the lateapoptotic stage also absorb the luminal food-derived antigens and their antibody complexes in the rat small intestine [43,44]. On late-apoptotic-stage epithelial cells in the rat jejunoileum, we detected (GlcNAc) [2][3][4] and -DGal(1-3)D-GalNAc exclusively [9].…”
mentioning
confidence: 92%